2011
DOI: 10.1073/pnas.1103317108
|View full text |Cite
|
Sign up to set email alerts
|

Detection and avoidance of a carnivore odor by prey

Abstract: Predator-prey relationships provide a classic paradigm for the study of innate animal behavior. Odors from carnivores elicit stereotyped fear and avoidance responses in rodents, although sensory mechanisms involved are largely unknown. Here, we identified a chemical produced by predators that activates a mouse olfactory receptor and produces an innate behavioral response. We purified this predator cue from bobcat urine and identified it to be a biogenic amine, 2-phenylethylamine. Quantitative HPLC analysis acr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

11
311
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 310 publications
(322 citation statements)
references
References 23 publications
11
311
0
Order By: Relevance
“…Indeed, Ferrero et al. (2011) recently showed that, contrary with noncarnivores, a large range of carnivores produce large amounts of the exact same chemical in their urine and that this chemical elicits antipredator responses in prey. Predator avoidance by prey species without prior experience to the predator is important, because innate antipredator responses will likely reduce the risk of prey populations suffer from high predation rates due to prey naivety if predators return (Berger et al.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, Ferrero et al. (2011) recently showed that, contrary with noncarnivores, a large range of carnivores produce large amounts of the exact same chemical in their urine and that this chemical elicits antipredator responses in prey. Predator avoidance by prey species without prior experience to the predator is important, because innate antipredator responses will likely reduce the risk of prey populations suffer from high predation rates due to prey naivety if predators return (Berger et al.…”
Section: Discussionmentioning
confidence: 99%
“…In vitro studies did not identify a high-affinity cadaverine receptor among mouse, rat, or human TAARs (18), although cadaverine reportedly activates TAAR-containing glomeruli in mice at high concentrations (8). Other mammalian TAARs also detect aversive amines; for example, isoamylamine (TAAR3) and 2-phenylethylamine (TAAR4), both likewise produced by decarboxylation of amino acids (16,18,19,32). Indeed, amines are an odor group that is chemically suited both to aquatic and airborne detection.…”
Section: Discussionmentioning
confidence: 99%
“…We reasoned that a zebrafish TAAR could mediate the cadaverine avoidance behavior because several rodent TAARs detect biogenic amines, including some highly aversive odors (16,(18)(19)(20). As a result of numerous gene-duplication events, the zebrafish TAAR family is large, with 112 receptors encoded by the zebrafish genome (17).…”
Section: Cadaverine and Other Diamines Activate Sparse Olfactory Sensorymentioning
confidence: 99%
See 1 more Smart Citation
“…olfactory receptor genes | Taar genes | nuclear organization T he mammalian olfactory system possesses enormous discriminatory power (1,2). It can distinguish a multitude of volatile odorants as having specific odors as well as elicit innate behavioral or physiological responses (3)(4)(5)(6).…”
mentioning
confidence: 99%